Nanostructures embedded on porous materials for the catalytic reduction of nitrophenols: a concise review - Zheng, Alvin Lim Teik; Teo, Ellie Yi Lih; Seenivasagam, Sivasangar; Yiu, Pang Hung; Boonyuen, Supakorn; Chung, Eric Lim Teik; Lease, Jacqueline; Andou, Yoshito (Springer, 2024)
The reduction of nitrophenols is a broadly accepted model for catalytic processes. Incorporating nanostructures into porous materials is becoming more widely acknowledged for its great importance. This strategy has attracted much interest because of its exceptional features imparted on the catalysts, offering enormous promise in accelerating the reduction of nitrophenols. In recent years, various nanostructures have been embedded to a wide range of porous materials, such as carbon, silica, metal-organic frameworks, and other inorganic materials. These porous frameworks possess unique physical and chemical characteristics, making them well-suited for catalytic applications. This thorough review begins by explaining the mechanism of nitrophenol reduction, exploring several nanostructures based on noble metals that are commonly used for catalytic reduction. Following that, a systematic description and comparison of nitrophenols catalytic reduction using various nanostructures on porous templates such as carbon-based, silica-based, zeolite-based, polymer-based, and metal-organic frameworks (MOF) were explained. In addition, this paper also examines several functional materials to enhance the catalytic reduction of nitrophenols. Herein, this write-up intends to narrow the knowledge gap on the recently synthesized catalysts and the practical requirements for removing nitrophenol. This write-up is hoped to offer valuable insights that can aid in the practical utilization of these catalysts for wastewater remediation applications.